ChemInform Abstract: Methodology for in situ Protection of Aldehydes and Ketones Using Trimethylsilyl Trifluoromethanesulfonate and Phosphines: Selective Alkylation and Reduction of Ketones, Esters, Amides, and Nitriles. Issue 25 (24th June 2014) - Yahata, Kenzo; Minami, Masaki; Yoshikawa, Yuki; Watanabe, Kei; Fujioka, Hiromichi
Abstract A new methodology for the selective reduction and alkylation of carbonyl nitrile groups in substrates also bearing more reactive aldehyde or ketone moieties is developed.